The product innovation of production enterprises and consumer preferences - Szymańska, Anna Irena (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2012)
Nowadays, the overriding aim of each enterprise is to satisfy consumers’ needs and to generate profits. Usually, companies realise these aims by having a wide-variety-of-products portfolio, and by using adequate marketing strategies or sale techniques. What is extremely important in this field is product innovation and adjusting the range of products to market needs.Innovation is especially important on the soft drinks market, which is the focus of the article. The typical feature of this market is fast moving of products, low production costs and a great variety of products accessible on the market. These factors cause that the soft drinks market is very demanding and competitive.